Using electronic purchasing to facilitate supply chain integration of manufacturing industry in China - Cheng, Dexin (2012)
In 2010, the internet-based procurement in China worth 4,500 billion of CNY (about 500 billion of Euros) with a growth rate of 22% compared to the previous year. B2B market was 3,800 billion CNY (about 433 billion of Euros), and the growth rate was 15.8%. Meanwhile the e-retail market finished at 513.1 billion of CNY (about 56.7 billion of Euros) and the market grown at a rate of 97.3%. Though e-purchasing is experiencing one high growth in China now, there are some limits of its applications. On one hand, not all companies, private consumers or government now fully understand the significance of e-purchasing and how to implement it, on the other hand, very little attention is paid on how to use e-purchasing to facilitate the integration of the supply chain management. This research takes using e-purchasing to facilitate the integration of the supply chain management in manufacturing industry in China as the target. This research will introduce the development of purchasing, the classifications and benefits of integrated e-purchasing, the implement strategy and tactic of e-purchasing, and how to use e-purchasing to help the integration of supply chain management. A Chinese case study is analysed and compared with a benchmarked company using models and research results of Bagchi and Skjoett-Lasen (2002). Results show that it is possible to improve the level of e-purchasing and supply chain integration of the analysed company and present a set of recommendations of how to do it. Limitations to the finding are presented as well as topics for future research.